Formal total synthesis of (-)-kumausallene - Das, Shyamsundar; Ramana, Chepuri V. (Tetrahedron, 2015)
Deacetylkumausyne-a penultimate intermediate in Tang's total synthesis of (-)-kumausallene has been synthesized employing a chiral pool approach and thus culminating in a formal total synthesis of kumausallene. The opening of an epoxide with alkyne (use of Birch reduction for the selective construction of E-pent-3-enyl group) and C-allylation have been used to introduce the pendant alkenyl side chains. Initial attempts to execute an alternative to Tang's route comprising a prior installation of the bromoallene unit via bromoetherification and subsequent S(N)2 displacement are unsuccessful. To overcome this, an alternative approach was developed to arrive at Deacetylkumausyne (another natural product that has been synthesized and characterized by Tang's group). Thus, this overall exercise has culminated in a formal total synthesis of (-)-kumausallene. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF natural products; Chiral pool; Deacetylkumausyne; Total synthesis; Wittig reaction